Asuhan Kebidanan Antenatal Pada Ny “S” Dengan Hiperemesis Gravidarum Tingkat I di Rumah Sakit Bhayangkara Kota Makassar - Siska, Siska; Nurhaedah, Nurhaedah; Ekawati, Nur; Hariati, Andi; Aotari, Wanti (JIMAD : Jurnal Ilmiah Multidisiplin, 2023)
Data obtained at the South Sulawesi Provincial Office of the number of maternal deaths in 2014 as many as 77 people with the most common cause is bleeding which is 40 people (51.94%), hypertension in pregnancy 21 people (27.27%), infection 1 person (1.29%) and other causes 15 people (19.48%). Data obtained from the Medical Record of Bhayangkara Makassar Hospital from the period January to December 2017 the incidence of Hyperemesis Gravidarum 10 people out of 450 (2.22%) while January to December 2018 the incidence of Hyperemesis Gravidarum 4 people out of 240 pregnant women (1.67%). The aim is to carry out midwifery care on Mrs. "S" pregnancy 14 weeks 4 days with Hyperemesis Gravidarum level I at Bhayangkara Makassar Hospital by using the Midwifery Management approach according to the authority of the midwife. This type of research is a case study and the methods used are literature study, case study, documentation study, discussion. The results of the evaluation after treatment on August 07, 2018, namely the general condition of the mother has improved, nausea and vomiting has decreased, vital signs are normal, dehydration has been resolved, abdominal enlargement according to gestational age and the mother understands the explanation and recommendations that have been given.